El diccionario más importante de la RAE no está impreso - Carriscondo Esquivel, Francisco M.; Carpi, Elena (El Colegio de México, 2019)
In the fifth volume of the Diccionario de autoridades (1737), a revised and corrected supplement of the entire work was announced, a plan later displaced by the project of a second edition, of which only the first volume would be published. For reasons that will be explained opportunely, the complete publication of theproposed second edition was posponed to a later date, until it was finally written off as unfeasible. The question arises, however, as to what became of the materials that were to make up the rest of the volumes. The present paper gives an answer to this question, as well as suggesting the reasons why the results of such an important piece of work only partially ever found their way into the printing shop.